China Digital Silk Road And Indonesia Digital Transformation - Muhammad Abdurrohim; Radita Gora Tayibnapis (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
The Belt and Road Initiative (BRI), the signature project of the Xi Jinping regime, has established a wide range of lofty goals that would usher in a new chapter of China's integration into the global market system and expand Chinese influence. Notably, China's now-powerful digital companies and cyberspace power actively sought a significant position in this massive statist effort under the policy banner of establishing a Digital Silk Road. Under this project, Beijing has multiple policy mechanisms to spread its digital power. Indonesia's enormous digital economy potential has become a significant target of this project. Using the qualitative method and analyzing two-level games by Robert D Putnam, this research will explain the relationship of Indonesian domestic actors concerning China's digital silk road. This research argues that the digital silk road in Indonesia has made more progress than other BRI projects because the DSR has integrated with the government, private sectors, and parliament's need for digital transformation. When the approval rating of domestic stakeholders is high, the success of the cooperation will be high too.